Women’s Leadership in Southeast Asia: Examining the Authentic Leadership Implementation Potency - Fajar Apriani; Dini Zulfiani (Policy & Governance Review, 2020)
Rapid economic growth in Asia has helped reduce gender inequality in several countries, especially those in Southeast Asia. This has led, among many other things, to the fact that women have higher opportunities to become leaders. Yet, in Southeast Asia the biggest challenge that remains is the tendency of “untrained” women in public leadership. Then the birth of women needs to get strategic support from the current system of leadership culture, that good life for women is the main pillar of women’s leadership requirements. This paper discusses the opportunities present for preparing Southeast Asian women to become future leaders from a number of authentic leader characteristics that they have. By using the content analysis method, the preliminary findings of this study is the existence of better gender relations, accompanied by the resilience and pragmatism of today’s location communities, bringing Southeast Asian women to a promising future leadership role. A number of characteristics of authentic leaders that have become the basis of women’s identity are actually the main capital to be prepared further through a number of educational efforts, assistance and training in order to increase knowledge, insight, organizational skills and self- confidence. Next, women leaders must be made. Women’s willingness and ability to adapt and develop stronger skills in the areas of emotional intelligence, empowerment, and power of influence place them in a strong position to use these advantages to propel them forward in leadership roles. Southeast Asian countries, especially those with a low human development index, have to begin to open up the need for a state led by women leaders who have the potential to represent a number of authentic leadership criteria to respond to the crisis of public confidence in the country’s leadership.